Penerapan Pendekatan Pembelajaran Active Deep Learner Experience Dalam Membangun Kemandirian Belajar Siswa Sekolah Dasar - Damai Ari Kontesa; Minsih; Djalal Fuadi (Elementary Teacher Education Program, Majalengka University, 2023)
Student learning independence is an important component in achieving learning success. However, student learning independence in schools is still not optimal so it is necessary to take a supportive learning approach, namely active deep learner experience. The purpose of this study is to analyze the application of the ADLX learning approach in building student learning independence in elementary schools. This research is a qualitative research with descriptive method. Data collection techniques through interviews, observation, and documentation. The data analysis technique uses an interactive analysis model consisting of three steps, namely data reduction, data presentation and conclusion drawing. The data validity test used triangulation of data sources. The results of the study suggest that the application of the active deep learner experience approach through individualization, interaction, observation, and reflective aspects, and is able to build student learning independence but in the aspects of interaction and individualization the application is still limited to a few students. Thus, the active deep learning experience approach can help foster student learning independence.